Many stimuli pull the necrotic trigger, an overview - Vanlangenakker, N; Vanden Berghe, T; Vandenabeele, P (Cell death and differentiation, 2012)
The lab of Jürg Tschopp was the first to report on the crucial role of receptor-interacting protein kinase 1 (RIPK1) in caspase-independent cell death. Because of this pioneer finding, regulated necrosis and in particular RIPK1/RIPK3 kinase-mediated necrosis, referred to as necroptosis, has become an intensively studied form of regulated cell death. Although necrosis was identified initially as a backup cell death program when apoptosis is blocked, it is now recognized as a cellular defense mechanism against viral infections and as being critically involved in ischemia-reperfusion damage. The observation that RIPK3 ablation rescues embryonic lethality in mice deficient in caspase-8 or Fas-associated-protein-via-a-death-domain demonstrates the crucial role of this apoptotic platform in the negative control of necroptosis during development. Here, we review and discuss commonalities and differences of the increasing list of inducers of regulated necrosis ranging from cytokines, pathogen-associated molecular patterns, to several forms of physicochemical cellular stress. Since the discovery of the crucial role of RIPK1 and RIPK3 in necroptosis, these kinases have become potential therapeutic targets. The availability of new pharmacological inhibitors and transgenic models will allow us to further document the important role of this form of cell death in degenerative, inflammatory and infectious diseases.